Identifikasi Waste Dengan Metode Value Stream Mapping (VSM) Pada Proses Pemeliharaan Kelapa Sawit Di PT. Perkebunan Nusantara IV Regional V - Rumondang Amelya Boru Marpaung; Christopher Davito Prabandewa Hertadi (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2026)
TThe process of oil palm plantation maintenance at PT Perkebunan Nusantara IV Regional V that is not running optimally can cause various activities that do not add value (waste), such as waiting time, unnecessary movements, excess processes, and inefficient use of resources. The process of oil palm plantation maintenance includes various activities such as disk and market pickers, wire rope pickers, pest control, castration, preliminary shoots, stock inventory, construction of garden facilities, fertilization, and insertion. The complexity of these activities has the potential to waste time, so exploration was carried out through field observations, interviews, documentation, and literature studies to classify activities into Value Added (VA) and Non Value Added (NVA). The current state results show a Value Added Time (VAT) of 8,636 hours and a Non Value Added Time (NVAT) of 2,344 hours, which is dominated by wasteful waiting, transportation, and unnecessary movements. Based on this analysis, a future state was compiled with recommendations for improvements in the form of adding a tool warehouse and water tank in the garden area, adding workers, and improving coordination and process flow. This proposal is estimated to reduce NVAT to 1,640 hours and increase the efficiency of the oil palm maintenance process. With a Process Cycle Efficiency (PCE) value of 78.65%, dominated by wasteful waiting, transportation, and unnecessary movements, a future state was developed with recommendations for improvements such as the addition of a tool warehouse and water tank in the plantation area, additional manpower, and improved coordination and process flow. This proposal is estimated to reduce NVAT to 1,640 hours and increase the PCE value to 81.23%, thereby increasing the efficiency of the oil palm maintenance process by 2.58%